A “Associação Hibakusha Brasil pela Paz” e os sobreviventes de Hiroshima e Nagasaki no Brasil - Loula, André Lopes (2017)
The objective of this work is to analyze the trajectory of the Association of the Victims of Atomic Bombs in Brazil, an institution founded in the city of São Paulo in 1984 - 39 years after the nuclear hecatomb of Hiroshima and Nagasaki. Through the analysis of the documentation contained in the collection of the Association and testimonies collected, the work gives visibility to the trajectory of people who survived the events that occurred in Hiroshima and Nagasaki, respectively, on August 6 and 9, 1945. The intention is to understand the role of this institution founded by survivors from the other side of the planet who contributed in Brazil for various reasons. Thus, it is intended to answer the following questions: what did they witness? How did they survive? How was the reconstruction of the city where they lived? Why did they immigrate to Brazil? Why the silence? This last inquiry looks to us for the conviviality with the trauma, one of the main dilemmas of the hibakushas (Japanese word for survivors of the bomb). Memory, the search for identity and the struggle to be recognized by the Japanese government as victims of this hecatomb are the main flags of the group of survivors. To this end, the hibakushas carry out various activities, such as lectures in schools and universities, in order to raise the awareness of younger generations about the risks of nuclear energy. We also tried to understand the events that preceded Hiroshima and Nagasaki. Analyzing the Meiji Era of 1868, modernizationof the land of the rising sun. The cultural change implemented in Japan. The imperialist race in the new world geopolitics, the United States, England, Germany, Japan, Russia, and France, all seeking to change their status quo in search of raw materials and consumers. All these characteristics will lead to 1st War and the 2nd War, which ends with nuclear weapons